2020
DOI: 10.15283/ijsc19138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cell Labeling on the Function of Human Pluripotent Stem Cell-Derived Cardiomyocytes

Abstract: Cell labeling technologies are required to monitor the fate of transplanted cells in vivo and to select target cells for the observation of certain changes in vitro. Human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs) have been transplanted for the treatment of heart injuries or used in vitro for preclinical cardiac safety assessments. Cardiomyocyte (CM) labeling has been used in these processes to facilitate target cell monitoring. However, the functional effect of the labeling agent on hiP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…For this reason, we analyzed the expression of several specific markers. As Choi et al have shown before for human pluripotent stem cell-derived cardiomyocytes [11], we were able to confirm that QDs do not affect the differentiation potential of human epidermal stem cells. All analyzed structural and functional markers were expressed at the same level for labeled and unlabeled EpiSCs.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…For this reason, we analyzed the expression of several specific markers. As Choi et al have shown before for human pluripotent stem cell-derived cardiomyocytes [11], we were able to confirm that QDs do not affect the differentiation potential of human epidermal stem cells. All analyzed structural and functional markers were expressed at the same level for labeled and unlabeled EpiSCs.…”
Section: Discussionsupporting
confidence: 85%
“…In a previous study, we reported no adverse effects of CdSe/ZnS QD labeling on the differentiation potential of adult stem cells isolated from rat pancreas [9]. Similar observations for other stem cell types such as embryonic stem cells, induced pluripotent stem cells or mesenchymal ones have recently been published [10][11][12]. Intriguingly, others have noted changes in the differentiation profile of stem cells after labeling with nanoparticles such as the inhibition of osteogenesis with QD labeled bone marrow mesenchymal stem cells [13][14][15].…”
Section: Introductionsupporting
confidence: 77%